Notes and News - Tracey, Hugh (International Library of African Music, 1961)
The Committee of Fine Arts and the Humanities of the African Studies Association - A new writers’ and artists’ club - African Music Society Exhibition of Paintings - The Royal Anthropological Institute - Some of the songs . . . - The American Society of African Culture - A conference on “The Arts of Africa” - The sixth annual meeting of the Society for Ethnomusicology - Doctorate awarded to the Rev. A. M. Jones - Africa interests American readers - Pygmies Retreat into the Congo Forests -Cultural Crisis in Underdeveloped Countries - Kwanongoma College - African Music draws increasing American interest - The National Theatre Organisation - Music in East Africa—Publishers please note—Course on African Arts and Music - Diploma.
Keywords: African Music